Splanchnic vein thrombosis and myeloproliferative neoplasms: molecular-driven diagnosis and long-term treatment - Stefano, Valerio De; Qi, Xingshun; Betti, Silvia; Rossi, Elena (Thrombosis and Haemostasis, 2016)
Splanchnic vein thrombosis (SVT) encompasses Budd-Chiari syndrome (BCS), extrahepatic portal vein obstruction (EHPVO), and mesenteric vein thrombosis. Philadelphia-negative myeloproliferative neoplasms (MPNS) are the leading systemic cause of non-cirrhotic and non-malignant SVT and are diagnosed in 40 % of BCS patients and one-third of EHPVO patients. In SVT patients the molecular marker JAK2 V617F is detectable up to 87 % of those with overt MPN and up to 26 % of those without. In the latter, other MPN molecular markers, such as mutations in JAK2 exon 12, CALR and MPL genes, are extremely rare. Immediate anticoagulation with heparin is used to treat acute patients. Upon clinical deterioration, catheter-directed thrombolysis or a transjugular intrahepatic portosystemic shunt is used in conjunction with anticoagulation. Orthotopic liver transplantation is the only reliable option in BCS patients with a lack of a response to other treatments, without contraindication due to MPN. Long-term oral anticoagulation with vitamin K–antagonists (VKA) is recommended in all SVT patients with the MPN-related permanent prothrombotic state; the benefits of adding aspirin to VKA are uncertain. Cytoreduction is warranted in all SVT patients with an overt MPN, but its appropriateness is doubtful in those with molecular MPN without hypercythaemia.
Keywords: Budd-Chiari syndrome; extrahepatic portal vein obstruction; mesenteric vein thrombosis; Philadelphia-negative myeloproliferative neoplasms; antithrombotic treatment